New types of -Open Sets and Associated Weak Separation Axioms (JOURNAL OF ADVANCES IN MATHEMATICS, 2016)
Pal and Bhattacharyya (1996)introduced the notion of pre--open sets.In this paper, we consider the class of pre--open sets in topological spaces and investigate some of their properties. Also,we present and study some weak separation axiomsby involving the notion of pre--open sets.